Barriers to accessing mental health services for women with perinatal mental illness: systematic review and meta-synthesis of qualitative studies in the UK - Megan Sambrook Smith; Vanessa Lawrence; Euan Sadler; Abigail Easter (BMJ Open)
Objective Lack of access to mental health services during the perinatal period is a significant public health concern in the UK. Barriers to accessing services may occur at multiple points in the care pathway. However, no previous reviews have investigated multilevel system barriers or how they might interact to prevent women from accessing services. This review examines women, their family members’ and healthcare providers’ perspectives of barriers to accessing mental health services for women with perinatal mental illness in the UK.Design A systematic review and meta-synthesis of qualitative studies.Data sources Qualitative studies, published between January 2007 and September 2018, were identified in MEDLINE, PsycINFO, EMBASE and CINAHL electronic databases, handsearching of reference lists and citation tracking of included studies. Papers eligible for inclusion were conducted in the UK, used qualitative methods and were focused on women, family or healthcare providers working with/or at risk of perinatal mental health conditions. Quality assessment was conducted using the Critical Appraisal Skills Programme for qualitative studies.Results Of 9882 papers identified, 35 studies met the inclusion criteria. Reporting of emergent themes was informed by an existing multilevel conceptual model. Barriers to accessing mental health services for women with perinatal mental illness were identified at four levels: Individual (eg, stigma, poor awareness), organisational (eg, resource inadequacies, service fragmentation), sociocultural (eg, language/cultural barriers) and structural (eg, unclear policy) levels.Conclusions Complex, interlinking, multilevel barriers to accessing mental health services for women with perinatal mental illness exist. To improve access to mental healthcare for women with perinatal mental illness multilevel strategies are recommended which address individual, organisational, sociocultural and structural-level barriers at different stages of the care pathway.PROSPERO registration number CRD42017060389.